AFM and SEM Study on Crystallographic and Topographical Evolutions of Wet-Etched Patterned Sapphire Substrate (PSS): Part II. Cone-Shaped PSS Etched in H2SO4 and H3PO4 Mixture with Varying Volume Ratio at 230°C. (1st January 2017) - Shen, Jian; Zhang, Dan; Wang, You; Gan, Yang
Abstract : Here we present a systematic study on crystallographic and topographical evolutions as well as etching rates of crystallographic planes of cone-shaped patterned sapphire substrate (PSS) etched in H2 SO4 and H3 PO4 mixture with a wide range of volume ratios (H2 SO4 :H3 PO4 = 1:0, 5:1, 3:1, 1:1, 1:3, and 0:1) at 230°C. The Miller indexes of four major exposed crystallographic planes were determined as S1 {1 1 ¯ 0 5}, S3 {4 5 ¯ 1 38}, S4 {1 1 ¯ 0 12}, and S6 {1 1 ¯ 0 8}. The etching rates of crystallographic planes follow the order S1 > S3 > S4 > c plane for H2 SO4 and H3 PO4 mixtures as well as S1 > S6 > c plane for H3 PO4 . A larger volume ratio (higher H2 SO4 concentration) favors a higher etching rate of c -plane and conversely lower etching rates of S1 -, S3 -, and S4 -planes, thus causing a larger filling factor with the largest filling factor of 0.93 obtained at the volume ratio of 5:1. This work will contribute to revealing the etching mechanism and fabricating optimized PSS for enhanced performance of light-emitting diodes.